PENGARUH STRUKTUR KEPEMILIKAN, FREE CASH FLOW, STRUKTUR ASET, DAN KEBIJAKAN DIVIDEN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFAR DI BURSA EFEK INDONESIA (BEI) - Deni Akbar; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to partially and simultaneously influence. Managerial Ownership, Institutional Ownership, Free Cash Flow, Asset Structure, and Dividend Policy to Debt Policy in sub sector otomotif and component companies listed in Indonesia Stock Exchange (BEI) Period 2010-2014. Where independent variable in this research is managerial ownership, institutional ownership, free cash flow, asset structure, dividend policy, and debt policy dependent variable. The method used to observe the effect of capital structure to the company's value is by using multiple linear regression.This study uses secondary data from the financial statements of companies sampled and sampling using purposive sampling techniques. Classic assumption test in this study include normality test, multicollinearity, heterocedasticity test, autocorrelation test. Analysis of data using the multiple linear regression analysis, t-test, f, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 16.The results showed that the variables managerial ownership,and institusial ownership partially (t test) significantly affects on the debt policy in a sub-sector of otomotif and component listed in the Indonesia Stock Exchange (BEI), while the variable free cash flow, asset structure, and devidend policy no significant effect on the debt policy in a sub-sector of otomotif and component listed in the Indonesia Stock Exchange (BEI). The results of the study simultaneously (f test) showed a significant effect of the variable managerial ownership, institusional ownership,free cash flow, asset structure and dividend policy on the debt policy in pulp and paper subsectors listed in the Indonesia Stock Exchange (BEI).Keywords: managerial ownership, institutional ownership, free cash flow, asset structure, dividend policy, debt policy